2018
DOI: 10.1534/genetics.118.300863
|View full text |Cite
|
Sign up to set email alerts
|

The UPRmt Protects Caenorhabditis elegans from Mitochondrial Dysfunction by Upregulating Specific Enzymes of the Mevalonate Pathway

Abstract: The mevalonate pathway is the primary target of the cholesterol-lowering drugs statins, some of the most widely prescribed medicines of all time. The pathway's enzymes not only catalyze the synthesis of cholesterol but also of diverse metabolites such as mitochondrial electron carriers and isoprenyls. Recently, it has been shown that one type of mitochondrial stress response, the UPR, can protect yeast, , and cultured human cells from the deleterious effects of mevalonate pathway inhibition by statins. The mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 77 publications
1
23
0
Order By: Relevance
“…In our study, the HMGCS-1 protein level was increased in SHSY5Y cells after treated with 20 µM Aβ 25-35 for 4 h, and after inhibiting the mevalonate pathway by HMGCS-1 siRNA or simvastatin in SHSY5Y cells treated with Aβ 25-35 , the expression of UPRmt related proteins were decreased. This is consistent with the researches in C. elegans that the UPRmt upregulates the expression of HMGS-1 (Oks et al, 2018), and inhibition of the mevalonate pathway through the hmgr-1 deletion mutant, hmgs-1 gene inactivation or statins prevents the activation of UPRmt (Liu et al, 2014;Ranji et al, 2014). We also found that inactivation of HMGCS-1 by siRNAs has no effect on the UPRmt reaction in SHSY5Y cells without Aβ treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the HMGCS-1 protein level was increased in SHSY5Y cells after treated with 20 µM Aβ 25-35 for 4 h, and after inhibiting the mevalonate pathway by HMGCS-1 siRNA or simvastatin in SHSY5Y cells treated with Aβ 25-35 , the expression of UPRmt related proteins were decreased. This is consistent with the researches in C. elegans that the UPRmt upregulates the expression of HMGS-1 (Oks et al, 2018), and inhibition of the mevalonate pathway through the hmgr-1 deletion mutant, hmgs-1 gene inactivation or statins prevents the activation of UPRmt (Liu et al, 2014;Ranji et al, 2014). We also found that inactivation of HMGCS-1 by siRNAs has no effect on the UPRmt reaction in SHSY5Y cells without Aβ treatment.…”
Section: Discussionsupporting
confidence: 92%
“…3-hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase is the rate-limiting enzyme in the mevalonate pathway; statins inhibit this enzyme to lower plasma cholesterol levels. Upon treatment with statins, C. elegans fail to sense mitochondrial damage and to activate the UPRmt (Liu et al, 2014;Ranji et al, 2014;Oks et al, 2018). Inactivation of the hmgs-1 gene, which encodes HMG-CoA synthase, renders C. elegans to lose the capability to respond to mitochondrial dysfunction and to inhibit antimycin-induced UPRmt induction (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…ATFS‐1 represses the transcription of genes encoding oxidative phosphorylation components and TCA cycle enzymes but increases the transcription of glycolytic enzyme genes, thus, maintaining overall ATP production. Furthermore, ATFS‐1 regulates the biosynthesis of certain lipid species 49,50 . In addition to this global metabolic adaption, ATFS‐1 promotes oxidative phosphorylation complex assembly and an increase in protective mitochondrial chaperones and proteases, which is designed to improve the health of the mitochondrial proteome 11,51 .…”
Section: Discussionmentioning
confidence: 99%
“…ATFS-1 represses the transcription of oxidative phosphorylation components and TCA cycle enzyme genes but increases the transcription of glycolysis enzyme genes, thus maintaining overall ATP production. Furthermore, ATFS-1 regulates the biosynthesis of certain lipid species (32,33). In addition to this metabolic adaption, ATFS-1 promotes oxidative phosphorylation complex assembly and an increase of protective mitochondrial chaperones and proteases designed to improve the health of mitochondrial proteome (9,34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this metabolic adaption, ATFS-1 promotes oxidative phosphorylation complex assembly and an increase of protective mitochondrial chaperones and proteases designed to improve the health of mitochondrial proteome (9,34). Importantly, this global change is beneficial to certain types of stresses or infection (32,33,(35)(36)(37), but is potentially harmful to others (38,39). Intriguingly, skeletal muscles of chronic alcohol users were reported to exhibit a reduction of aerobic metabolism and an increase of anaerobic metabolism (40).…”
Section: Discussionmentioning
confidence: 99%